The Impact of Intellectual Property Law on Startups and SMEs: A Systematic Review - Zulkifli, Zulkifli; Yulia, Yulia; Almusawir, Almusawir; Abdurrifai, Abdurrifai; Rizal, Andi (Journal of Posthumanism, 2025)
Intellectual property (IP) law is one of the main instruments promoting innovation and the competitive advantages with which startups and small and medium enterprises (SMEs) can solidify their market standing. This study aims to analyze how IP protection stimulates innovation, secures investments, and boosts market competitiveness using patents, trademarks, copyrights, and trade secrets. This research used the Preferred Reporting Items for Systematic Reviews and Meta - Analysis (PRISMA) to conduct a systematic literature review, ensuring transparency, accountability, and a systematic methodology in selecting and analyzing relevant articles. The findings indicate that whereas strong protection under the IP regime motivates the innovation process through research and development (R&D), it produces heavy entry costs and legal consequences, whose burdens are keenly felt by those firms that have limited resources. Also, jurisdiction inconsistencies and deficient enforcement mechanisms worsen the infringement risk picture, limiting start-ups' ability to protect their intellectual assets. New trends such as open innovation, collaboratively licensed models, and blockchain-based IPR setups are also elaborated on in the study. These would necessarily challenge the very fundamental patent-based regimes and require new modes for regulation. The study states the necessity for change into a more inclusive and flexible system of IP protection balanced between restricted and open access in such a way that startups and SMEs can certainly and favorably make use of intellectual property as a strategic asset for sustainable economic growth.